Gestão de crise de imagem: um estudo de caso de uma universidade federal brasileira - Vieira, Maria Leticia Fabiano Rodrigues Vale (2019)
The purpose of this master’s thesis is to analyze how the organizational image management is done by a Brazilian federal university. In order to overcome the challenges of competitive pressures, low government spending for higher education institutions, and strong changes in the educational environment, institutions must to build strong channels and open relationships with the public before the crisis comes. Crisis management must not be understood as a way of escape, but as a window of opportunity to rebuild the image and strengthen the confidence in the institution. In a case study research design using qualitative methods, this study makes a triangulation of data collection instruments, as following: (1) documentary research, (2) semi-structured interview, and (3) structured interview. In the semi-structured interview, data were collected from the individual corresponding to the charge of leadership and two technical servants of the Communication Advisory staff. In a structured way, only the leader was interviewed. He is the actor who answers, directly and hierarchically, to everything could be regarded to the management of crisis situations. Finally, a documentary research was made to access and to collect open records and documents, such as news and notes, associated with the latest crisis situation reported by respondents – a shooting threat on the University. Thus, for all data collection instruments, content analysis was used in light of Bardin (1977). The main results show that, in general, an Advisory Office works to answer the demands of press groups, lacking clear and basic prevention measures. Despite the context of a image crises be taken into consideration, their actions are still purposed to remedy the contingencies that arises as crises to the institution, especially by the press. The analytical effort to combine data collection instruments was facilitated with the identified level of capacity for crisis management by the Advisory. This is the first level, the most passive one. It is little committed to institutionalized main practices and guidelines. Thus, this study aims to contribute to the construction of the current scenario of the Advisory regard the crisis management, as well as to help the institution to improve its processes.